Strategi Pengurus dalam Penyelenggaraan Kesejahteraan Sosial untuk Menuju Karang Taruna Berprestasi Nasional - Warto Warto; Suryani Suryani (Jurnal Penelitian Kesejahteraan Sosial, 2018)
This research was aimed to reveal the strategy of youth organization in implementing the social welfare up to national level achievement. The research was conducted at Karang Taruna Dipo Ratna Muda in Guwosari Village, Pajangan Subdistrict, Bantul Regency, under certain consideration that the youth organization had ever achieved the first champion in national level for two times (in 2009 and in 2016). Data collection used interviews guide, observation, and documents study. Data was analyzed descriptively qualitatively. Research results showed that there were three strategies which were run by the management of Dipo Ratna Muda youth organization in implementing the social welfare namely: 1. Developing the values of heroism spirit in its dedication. 2. Multiplying the amount and variation of educational, economical, productive, recreative, and social activities. 3. Activating the entire youth organization units asthe implementationâ€™s spearhead of their activities. In implementing the social welfare, the supporting factors in achieving the nationally success were the existence of the dedication spirit of the youth, loyalty off all members and the support of village government in either providing secretariate office and fund for operation. There was an obstacle factor in work coordination among organization members namely the difficulty to spare time for a meeting of coordination because of each member personal activities. It is recomended that their strategy could be used as a reference by both the Ministry of Social in coaching such organizations and by other youth organization leaders in their effort to develop and to promote the youth organizations that function as government partners in handling social welfare issues.Â